Answer:
-1/12
Explanation:
We are given the following expression and we are to simplify it leaving the answer in the form of an improper fraction:
![\frac {1} {2} + \frac {1} {6} - \frac {3} {4}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t3m95yxb6dq85kkwm71izuzv9oahbxuilr.png)
We will start by adding the first two fractions by taking their LCM and making it a single fraction to simplify the expression further:
![\frac {1} {2} + \frac {1} {6} = \frac {1 + 3} {6} = \frac {4} {6} = \frac {2} {3}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/iz30bwyckjie282p3ektsxzibiy9qyfta2.png)
Now subtracting
from the result obtained above:
![\frac {2} {3}-\frac {3} {4} = (2(4)-3(3))/(12) =(8-9)/(12) =-(1)/(12)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6yj6p1skiqfdaf253892q3ltkkvm6k4k82.png)